Analisis Permasalahan Pembangunan Desa Tanjung Saribu dan Strategi Solusi Berkelanjutan - Sunday Ade Sitorus; Fiktor Sihombing; Firman Mulana Silaban; Windi Klara Sinaga; Regen Boy Saputra; SUNDAY ADE SITORUS (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service and Empowerment Lecture Program is designed to achieve multidimensional objectives that benefit students, communities, and universities. For students, the program aims to deepen interdisciplinary knowledge and skills, enhance understanding of the application of science, technology, and art in development, and improve problem-solving abilities through hands-on field experience. The program yielded tangible results, including a 25% increase in community members' understanding of financial management, improved agricultural practices leading to higher crop yields, and the successful establishment of a local cooperative that supports ongoing economic activities in the village. In conclusion, the community service activities effectively contributed to the socio-economic development of Desa Tanjung Saribu. The initiatives empowered the local community with the skills and knowledge necessary to sustain their progress, fostering a more self-reliant and resilient community.